Active gellan gum/purple sweet potato composite films capable of monitoring pH variations. (August 2017) - Wei, Yu-Chia; Cheng, Chia-Hsiung; Ho, Yi-Cheng; Tsai, Min-Lang; Mi, Fwu-Long
Abstract: Purple sweet potato (PSP) is a root crop containing higher levels of certain nutrients including anthocyanins. PSP anthocyanins are known to have antioxidant activity and many health benefits. In this study, PSP anthocyanins were identified and quantitated by HPLC-DAD-ESI/MS and UPLC-Q-TOF-MS analysis. The color change at different pH values was measured through the CIELab scale. Gellan gum was combined with PSP to obtain stable gellan gum/PSP composite films. The composite films exhibited reduced hydrophilicity, swelling property and water vapor transmission rates (WVTR) as compared to the films prepared from gellan gum alone. PSP also increased the mechanical property and antioxidant activity of the composite films. The active packaging films were able to control the PSP anthocyanins release in simulated gastrointestinal fluids at pH 2.0, 6.0 and 7.4. Application of the intelligent films was performed by colorimetric detection of the pH changes caused by growing Escherichia coli on nutrient agar plates. When attaching the films on the cover of petri dishes, the films changed their color from purple (initial) to blue (6 h) and to yellow-green (24 h) with the growth of bacteria and digestion of proteins to produce volatile amines. The gellan gum/PSP composite film may have potential as an active and intelligent packaging material showing enhanced antioxidant, water-resistant and mechanical properties, and may be served as an easy-to-use indicator system to detect the spoilage of protein-rich foods caused by the growth of bacteria. Graphical abstract: Highlights: Gellan gum was blended with PSP to obtain gellan gum/PSP composite films. PSP reduced hydrophilicity and swelling of gellan gum films. PSP improved mechanical strength and antioxidant activity of gellan gum films. the composite films can be used to monitor pH variations.